Request for review of materials for supply installation, testing & commissioning of davit arm for BRACU (RFA-002_Rev.0) - Fabcons Construction & Fabrication (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.